Relationship between source rock development and petroleum accumulation in the Erlian Basin, northern China. (12th July 2018) - Ding, Xiujian; Liu, Guangdi; Imin, Ablimit; Rexit, Madiniyat; Gao, Changhai; Jiang, Hang
Abstract: The Wuli and Saihan sags in the Erlian Basin, the most petroliferous basin in northern China, were analysed with bulk geochemical analysis, carbon isotopic composition, microthermometry of fluid inclusions, and basin modelling to characterize the organic matter abundance and composition, to construct source rock development models, and to reveal the relationship between source rock development and hydrocarbon accumulation. The samples display wide variations in total organic carbon content and Rock‐Eval indices, suggesting heterogeneity of organic matter richness and type. The Wuli Sag has oxic depositional environment, high productivity, and high total organic carbon content; the effective oil source rocks are mainly distributed in the deep sag where the productivity is high; and there is plenty of organic matter left and preserved after degradation. In the Saihan Sag, there is a small amount of organic matter deposited because of low productivity; the effective oil source rocks are mainly distributed in the slope by the deep sag where the reducing degree is the strongest. The source rock development models controlled the geochemical characteristics and distribution of source rocks, which are the keys to hydrocarbon potential and accumulation. The oil of Wuli Sag is mainly distributed in the deep sag, whereas the oil of Saihan Sag is mainly distributed in the slope by deep sag, which is in agreement with the previously effective oil source rocks distribution. In the strong division sags, the region where source rock distributed is beneficial to hydrocarbon accumulation. The conclusions may have important implications for petroleum exploration in other small lacustrine depositional systems.